2010
DOI: 10.1071/rd09033
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the function of fresh and frozen - thawed sex-sorted and non-sorted stallion spermatozoa using a heterologous oocyte binding assay

Abstract: The aim of the present study was to evaluate the potential oocyte binding ability and functional integrity of fresh or frozen-thawed, sex-sorted or non-sorted stallion spermatozoa. In the absence of effective IVF procedures in the horse, a heterologous sperm-binding assay was used as an indicator of fertilising capacity to assess differences in the ability of stallion spermatozoa to bind to bovine oocytes. The functional integrity of four treatment groups was assessed: (1) fresh non-sorted spermatozoa; (2) fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…This result agrees the only study that described heterologous IVF using cryopreserved dolphin spermatozoa, in which maximum attachment and binding were achieved at 2 h of co-incubation with zona-free hamster oocytes [9]. Similar times are used in co-incubation studies of other species [46][47][48][49].…”
Section: Dolphin Spermatozoa Interact and Penetrate Both Zona Intact supporting
confidence: 84%
“…This result agrees the only study that described heterologous IVF using cryopreserved dolphin spermatozoa, in which maximum attachment and binding were achieved at 2 h of co-incubation with zona-free hamster oocytes [9]. Similar times are used in co-incubation studies of other species [46][47][48][49].…”
Section: Dolphin Spermatozoa Interact and Penetrate Both Zona Intact supporting
confidence: 84%
“…4D). This assay has recently been developed to address difficulties associated with the acquisition of sufficient horse oocytes and, importantly, has been used to assess stallion sperm capacitation status (Clulow et al 2010, Coutinho da Silva et al 2012. The use of this assay in our study demonstrated that media containing PVA and mbcd supported the highest levels of ZP binding with an average of 119.4 sperm bound to the ZP of each bovine oocyte, a result that significantly exceeded the number of sperm bound after incubation in NC conditions (11.6 cells/oocyte).…”
Section: Discussionmentioning
confidence: 99%
“…The use of this assay in our study demonstrated that media containing PVA and mbcd supported the highest levels of ZP binding with an average of 119.4 sperm bound to the ZP of each bovine oocyte, a result that significantly exceeded the number of sperm bound after incubation in NC conditions (11.6 cells/oocyte). The gamete co-incubation method used in these studies was adapted from that established by Clulow et al (2010) in studies of fresh and frozen, sex-sorted and non-sorted stallion spermatozoa. These authors demonstrated that after incubation in TALP and co-incubation with heterologous bovine oocytes, an average of fewer than 30 sperm were bound to each oocyte (Clulow et al 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations